Changes in online course designs: Before, during, and after the pandemic - Misiejuk, Kamila; Ness, Ingunn Johanne; Gray, Robert; Wasson, Barbara (Frontiers in Education, 2023)
The switch to emergency remote teaching during the COVID-19 pandemic became for many university instructors a necessity to familiarise themselves with the institution’s online learning management system (LMS). This switch to online teaching made learning activities, course design patterns, and pedagogical approaches more visible than during face-to-face teaching. Furthermore, the process of translating physical learning activities to the digital space was challenging and needed institutional and leadership support. This paper presents an analysis of the changes made to the learning designs of 102 courses in a university’s LMS before, during, and after the pandemic. Using descriptive statistics and Epistemic Network Analysis we used LMS data to explore the use of LMS features revealing not only the overall university trends, but also faculty differences. In addition, we compared the learning activities as described in course descriptions with the actual learning activities designed in the LMS. Our findings show that although the switch to emergency remote teaching forced many instructors to change the learning designs of their courses, some instructors reverted back to their pre-pandemic learning designs after the pandemic, while other instructors did not change their learning design during the pandemic at all. In addition, we identified a positive trend of an increased use of activity features in the learning management system. Finally, we reflected on the importance of the university leadership supporting the digital transformation.